Education that Inspires Creating the Future of Human Education - Sequeira, Cinderella (JOURNAL OF INDIAN EDUCATION, 2021)
The aim of this paper is to visit the future of education, which is reduced to a well-marketed knowledge certifying agency rather than helping students of the future to evolve into authentic human beings harmonising life, relationships and societal goals, to create inspired learners who are propelled into contributing to the building of a better world. The ultimate teleology of education is the seeking of a harmonious goal of human education; the necessity is to provide an education that is oriented towards being more human, that aims to promote critical thinking and problem posing in education, that harmonises one’s relationships with oneself, the other, planet earth as our common home and – in terms of the future – harmonious co-existence of humans and technology. Three important derailments in modern education will be dealt with, namely, (a) the lack of subjectivity and critical thinking in education, (b) the mechanical system of education and (c) the emphasis on the production of a marketable student. The paper concludes with the necessity of reviewing our fundamental educational philosophy in order to ensure that we, as a community do not miss out on the very nature and purpose of education.